Social Accounting as an Enabling Tool to Develop Collective Organizational Citizenship Behavior in the Diocese of Bilbao - Retolaza, Jose Luis; Aguado, Ricardo; San-Jose, Leire (Frontiers in Psychology, 2020)
Religious oriented organizations (ROOs) have frequently higher levels of motivation among their employees, because the aims of ROOs and those of collaborators and stakeholders are usually aligned. However, sometimes, when the management of ROOs becomes professionalized, tensions between aims and efficiency are more frequent, and productivity levels start to decline. The most widespread current management theories are focused on profit maximization and are not especially helpful to religious organizations which try to enhance their productivity levels and, at the same time, achive their mission and aims. In order to fill this gap, in this research, we will develop two main concepts: social accounting and organizational citizenship behavior (OCB). We will propose the use of social accounting to calculate the social value generated by ROOs and, from that point, build new indicators able to measure the organizational citizenship behavior (OCB) of collaborators working in ROOs. We will exemplify this theoretical development with the actual case of the diocese of Bilbao. In short, the main objectives of this work are two. The first objective is the development of a theoretical framework able to enhance the levels of social value creation inside religious (and socially oriented) organizations using social accounting. The second objective is the use of data from the 16 educative centers of the diocese of Bilbao to ilustrate that social accounting is a valid tool to measure social value. Additionally, we will show that social accounting can be a tool to assess management decisions in order to enhance organizational and individual OCB in ROOs and, in this way, generate moral satisfaction for employees and collaborators in their organizations.